2010
DOI: 10.1189/jlb.1109764
|View full text |Cite
|
Sign up to set email alerts
|

Human adenosine deaminase 2 induces differentiation of monocytes into macrophages and stimulates proliferation of T helper cells and macrophages

Abstract: ADAs play a pivotal role in regulating the level of adenosine, a signaling molecule controlling a variety of cellular responses by binding to and activating four ADRs. Two enzymes, ADA1 and ADA2, are known to possess ADA activity in humans. Although the structure of ADA1 and its role in lymphocytic activation have been known for a long time, the structure and function of ADA2, a member of ADGF, remain enigmatic. Here, we found that ADA2 is secreted by monocytes undergoing differentiation into macrophages or DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
187
0
15

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(209 citation statements)
references
References 37 publications
7
187
0
15
Order By: Relevance
“…АДА-2 экспрессируется моноцитами/макро-фагами в ответ на инвазию патогенов (Mtb) в ме-ста с высокой концентрацией аденозина и низким pH [15]. У больных ФКТ по отсутствию связей между показателями АДА сыворотки и монону-клеаров можно предположить, что рост активно-сти внеклеточной АДА-2 происходит вследствие разрушения (лизиса) макрофагов.…”
Section: результаты и обсуждениеunclassified
See 2 more Smart Citations
“…АДА-2 экспрессируется моноцитами/макро-фагами в ответ на инвазию патогенов (Mtb) в ме-ста с высокой концентрацией аденозина и низким pH [15]. У больных ФКТ по отсутствию связей между показателями АДА сыворотки и монону-клеаров можно предположить, что рост активно-сти внеклеточной АДА-2 происходит вследствие разрушения (лизиса) макрофагов.…”
Section: результаты и обсуждениеunclassified
“…Ключе-вые ферменты пуринового метаболизма -адено-зиндезаминаза (АДА и ее изоферменты -АДА-1 и АДА-2) и экто-5'-нуклеотидаза (5'-НК), кон-тролирующие уровень аденозина, играют важную роль в регуляции клеточного иммунитета [7]. АДА-1 увеличивает пролиферацию CD4 + T-клеток, стимулирует пролиферацию антиген-активи-рованных Т-клеток, продуцирующих IFNγ [15]. АДА-1 -в комплексе с протеином, идентифици-рованная как дипептидилпептидаза IV (DPPIV), присутствует в качестве эктоэнзима на различных клетках [6].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The disruption of cecr1a expression in mpx-GFP transgenic fish causes a marked reduction in neutrophil numbers. ADA2 is known to induce T-cell-dependent differentiation of monocytes into macrophages [12]. These observations suggest a role for ADA2 in differentiation of endothelial and myeloid cells.…”
Section: Pathogenesis Of Dada2mentioning
confidence: 98%
“…ADA2 normally has a much lower capacity to catalyze adenosine deamination than ADA1 [16]. ADA2 enzyme activity becomes optimal at high levels of adenosine, low pH and inflammation conditions [17,18], that can associated with lung cuntusion injury. We found that ADA2 became predominant isoenzyme in serum, which may be due to active tissue macrophages during lung contusion.…”
Section: Control (N=6)mentioning
confidence: 99%